Inland water quality monitoring with native bryophytes: A methodological review. (June 2015) - Debén, S.; Aboal, J.R.; Carballeira, A.; Cesa, M.; Real, C.; Fernández, J.A.
Abstract: Aquatic bryophytes are used as a simple, reliable and economic tool for passive biomonitoring of water quality. However, a harmonized protocol that would enable use of the method outside of the scientific field is not yet available. The aim of this literature review, which considers 73 articles published between 1979 and 2013, is to ascertain the current status of the technique and to evaluate the degree of standardization of each aspect of the method. The use of this tool is largely limited to Europe (80% of the articles reviewed). It has mainly been used to biomonitor inorganic (in 97% of the articles) and to a lesser extent organic contaminants (in 4% of the articles; note that the sum is greater than 100% because both inorganic and organic contaminants were studied in some studies). Methodological aspects were only considered in 15% of the articles. Moreover, 81% of the authors have only published one article on the topic and many different protocols have been used. As a result, the technique is not standardized, which hampers comparison of the results of different studies. Finally, we propose a protocol that would facilitate the use of the technique as a routine tool for monitoring the quality of inland waters.